The ACL Graft Has Different Cross-sectional Dimensions Compared With the Native ACL: Implications for Graft Impingement. (August 2016) - Thein, Ran; Spitzer, Elad; Doyle, John; Khamaisy, Saker; Nawabi, Danyal H.; Chawla, Harshvardhan; Lipman, Joseph D.; Pearle, Andrew D.
Background: Impingement of anterior cruciate ligament (ACL) grafts against the femoral notch and the posterior cruciate ligament (PCL) is thought to be influenced primarily by tunnel position and graft orientation. Recent data have implied that the native ACL is ribbon-shaped. Purpose: To evaluate the 3-dimensional shape and cross-sectional area of the native ACL versus the ACL graft and to compare the degree of impingement against the femoral notch and PCL. Study Design: Cross-sectional study; Level of evidence, 3. Methods: Bilateral knee magnetic resonance images were analyzed for 27 patients with unilateral bone–patellar tendon–bone (BPTB) ACL reconstruction performed via transtibial or anteromedial portal femoral tunneling techniques. Three-dimensional models of the ACL, PCL, femur, and tibia were digitally rendered. The cross-sectional area and dimensions of the native ACL and the reconstructed graft were determined at 3 equally spaced locations and compared via Wilcoxon-Mann-Whitney and Kruskal-Wallis tests. In addition, impingement of the ACL on the PCL and femoral notch was graded in 3 groups. Chi-square or Fisher exact tests were used to compare the proportional differences of impingement of the native and reconstructed ACL on the PCL and femoral notch, respectively. All analyses were performed using 2-sided hypothesis testing, with statistical significance at P < .05. Results: Cross-sectional areas at all 3 points on the ACL graft were significantly greater than those of the native ACL ( P < .001). The long- to short-axis ratio for the native ACL was significantly greater at each location compared with the corresponding locations along the ACL graft ( P < .001), implying that the native ACL is "flatter" than is an ACL graft. There were 19 operated knees (70%) with contact or impingement between the ACL graft and the femoral notch compared with zero knees with a native ACL ( P < .001). In addition, 22 operated knees (81%) showed contact or impingement between the ACL graft and the PCL, compared with 7 knees (26%) with a native ACL ( P < .001). No significant differences in impingement frequency were noted between the transtibial and anteromedial tunneling techniques for ACL graft specimens ( P > .05). Conclusion: Native ACLs have a smaller cross-sectional area, are "flatter, " and experience less incidence of impingement compared with anatomically placed BPTB ACL grafts.